2017
DOI: 10.3892/or.2017.5553
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p53 protein is a marker of poor prognosis in Mexican women with breast cancer

Abstract: Breast cancer (BC) is a disease with different clinical, histological and molecular characteristics, frequently presenting mutated tumour-suppressing genes and oncogenes. P53 is a known tumour suppressor that is often mutated in BC; several mutations in p53 inhibit its role as a transcriptional repressor of several oncogenes. Topoisomerase 2α (TOP2α) is a gene target of p53, and it is also a known target for anthracyclines. The aim of the present study, was to analyse the genetic alterations of p53 and TOP2α g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Mutant p53 proteins usually causes the accumulation of p53 protein at a very high levels, and the mutant p53 protein itself can inhibit normal p53 protein levels [ 11 ]. In recent years, several reports have shown that p53 expression can serve as a promising biomarker for predicting various tumors [ 14 19 ]. Many studies have also reported the prognostic value of p53 expression in RCC, but the results were still conflicting [ 20 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant p53 proteins usually causes the accumulation of p53 protein at a very high levels, and the mutant p53 protein itself can inhibit normal p53 protein levels [ 11 ]. In recent years, several reports have shown that p53 expression can serve as a promising biomarker for predicting various tumors [ 14 19 ]. Many studies have also reported the prognostic value of p53 expression in RCC, but the results were still conflicting [ 20 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant p53 cannot be effectively bound to DNA , and the p21 protein cannot act as the “stop signal” for cell division, which results in tumors formation [ 12 , 13 ]. It is reported that p53 expression predicts prognosis in various multiple cancer types including breast cancer [ 14 ], gastric cancer [ 15 ], multiple myeloma [ 16 ], colorectal cancer [ 17 ], cervical cancer [ 18 ], and oral cancer [ 19 ]. Many studies have investigated the prognostic role of p53 expression in RCC, but the results are conflicting [ 20 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…| 3425 between p53 overexpression and poor prognostic factors, an increased frequency of regional recurrence, and visceral metastasis in breast cancer patients, 50 and patients with triple-negative breast cancer showed p53 protein overexpression, which resulted in lower survival. 51 In our study, the expression of p53 was upregulated in anoikis-resistant NPC cells with highly invasive and metastatic characteristics. Inhibition of INHBB can activate TGF-β function through the interaction of TGF-β and p53, 52 which could further improve p53 levels in metastatic NPC cells ( Figure S3).…”
supporting
confidence: 47%
“…The functional switching of TGF‐β is partially caused by p53 mutation or p53 inactivation during cancer progression . A significant correlation existed between p53 overexpression and poor prognostic factors, an increased frequency of regional recurrence, and visceral metastasis in breast cancer patients, and patients with triple‐negative breast cancer showed p53 protein overexpression, which resulted in lower survival . In our study, the expression of p53 was upregulated in anoikis‐resistant NPC cells with highly invasive and metastatic characteristics.…”
Section: Discussionmentioning
confidence: 52%
“…A meta-analysis conducted by De-Ke Jiang et al concluded that TP53 Arg72 carriers can significantly reduce the risk of esophageal cancer ( 36 ). In contrast, Dimas-Gonzalez et al reported that p53 protein was up-regulated in breast cancer ( 37 ). The TP53 Arg72Pro CC genotype may contribute to an increased risk of CRC, especially for rectal cancer and among Asians ( 38 ).…”
Section: Discussionmentioning
confidence: 92%